EVALUATION OF SEVERAL WHEAT CULTIVARS IN RESPOND TO DIFFERENT TYPES OF FERTILIZERS INCLUDING BIO-FERTILIZER UNDER RAINFED CONDITIONS - O, Fathi A.; Tahir, D. Sh.; How, P. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The research was conducted during 2018-2019 growing season to study the growth and yield of various wheat cultivars under various methods of fertilizers application including bio-fertilizer under rainfed conditions of two different isohyets conditions. Randomized complete block design was applied with four replications. Potential grain yield is highly affected by the number of reproductive tillers; differences in final grain yield were highly and positively correlated to the number of tillers (r= 0.54**) and above ground biomass (r= 0.68**). The grain yield was about three times higher in Rikava location (3.19/1.01 t.ha-1). Both of Cihan and Adana99 wheat significantly produced higher grain yield (2.44 and 2.43 t.ha-1 respectively) followed by Tammoze and Italy, the Criso durum wheat was the inferior with only 1.65 t.ha-1 grain yield. DAP fertilizer (2.58 t.ha-1) was the best fertilizer treatment followed by YARA and BIO and all treatments were significantly higher than the check unit which produced only 1.7 t.ha-1. The interaction of Adana99 with DAP (2.79 t.ha-1) and Cihan with DAP (2.71 t.ha-1) recorded highest grain yield; these two cultivars with BIO fertilizer produced significant grain yield and each gave (2.5 t.ha-1). Financial analysis revealed the superiority of both Anana99 and Cihan cultivars with DAP fertilizer followed by BIO fertilizer as they contributed positively with the highest final revenue.